Spontaneous pneumomediastinum mimicking acute pericarditis. Issue 12 (4th December 2021) - Chaudhary, Haseeb; Yousaf, Zohaib; Nasir, Usama; Waheed, Tayyab; Syed, Khezar
Abstract: ST elevations on electrocardiogram (ECG) have a broad differential diagnosis that can vary from benign to more ominous pathologies. These include early repolarization, coronary vasospasm, acute pericarditis, ST‐elevation myocardial infarction, ventricular aneurysms, and dissecting aneurysm of the aorta reaching the pericardium. ST‐segment changes may also provide a clue to the presence of spontaneous pneumomediastinum (SPM). These ECG changes are seldom reported in literature. We describe two SPM cases with concomitant pneumopericardium that closely mimicked acute pericarditis with a deceptive clinical spectrum. Abstract : The atypical clinical presentation of pneumomediastinum may produce ECG changes. The ECG changes of pneumomediastinum can mimic acute pericarditis. Early recognition and appropriate treatment can lead to improved clinical outcomes.